Mexiletine Treatment for Neonatal LQT3 Syndrome: Case Report and Literature Review - Bagkaki, Alena; Tsoutsinos, Alexandros; Hatzidaki, Eleftheria; Tzatzarakis, Manolis; Parthenakis, Fragiskos; Germanakis, Ioannis (Frontiers in Pediatrics, 2021)
Background. Early diagnosis of Long QT type 3 (LQT3) syndrome during the neonatal period is of paramount clinical importance, provided the increased mortality and a mutation specific response to treatment compared to other more common types of LQT syndrome. Mexiletine, a sodium channel blocker, demonstrates a mutation specific QTc shortening effect in LQT3 syndrome patients. Case presentation. A neonate manifested marked QTc prolongation after birth, on electrocardiogram (ECG) recording performed due to positive family history of LQT3 syndrome genetically confirmed (SCN5A gene missense mutation Tyr1795Cys) and associated with sudden cardiac death in family members. The mexiletine QTc normalizing effect (QTc shortening from 537 to 443 ms), practical issues related to oral mexiletine treatment of our young patient along with literature review regarding identification and mexiletine treatment in infants with LQT3 syndrome are presented. Conclusions. Mexiletine could be considered in the treatment of high risk LQT3 patients already in the neonatal period in addition to b-blocker therapy. Availability of standardized commercial mexiletine pediatric formulas, serum mexiletine level analyses and future prospective studies are needed to evaluate the potential beneficial effect of early mexiletine treatment on the incidence of future acute cardiac events in this high risk LQT syndrome patients